Usefulness of Portable Device to Establish Differences in Muscle Oxygenation Between the Wingate Test and Graded Exercise Test: Effect of Gender on Anaerobic and Aerobic Capacity in Speed Skaters - Rębiś, Kinga; Sadowska, Dorota; Starczewski, Michal; Klusiewicz, Andrzej (Frontiers in Physiology, 2022)
The aim of this study was to compare the oxygenation response in the vastus lateralis muscle (SmO2) in two types of tests: supramaximal and maximal. Furthermore, gender differences in SmO2 response to test exercise were assessed and the usefulness of muscle oxygenation measurements in the assessment of anaerobic and aerobic capacity was determined. The Wingate test (WAnT) and the graded exercise test (GXT) to exhaustion were performed on a cycle ergometer to examine 13 female and 14 male speed skaters from the junior and U23 national teams. During both tests, SmO2 of the vastus lateralis muscle was recorded by near-infrared spectroscopy at baseline (at rest or post warm-up), at exercise, and during recovery. The most significant SmO2 indices (differences between baseline and post-exercise indices and half time for SmO2 to reach the maximal post-exercise value) were not significantly different between the tests. Gender was also not a differentiating factor in muscle oxygenation regardless of test type. In the GXT test, half time required for SmO2 to reach the maximal value correlated negatively with VO2max and test duration, thus confirming the usefulness of SmO2 measurements in the assessment of the aerobic capacity of speed skaters. In contrast, the WAnT test showed no significant correlations between exercise indices and muscle oxygenation indices. From the standpoint of the assessment of anaerobic capacity, SmO2 measurements showed little diagnostic value.